Identification of Types and Production Volume of Catched Fish at Pondokdadap Beach Fishing Port (PPP), Malang Regency - Muhammad Fikri Ariefandi; Andik Isdianto (Universitas Airlangga, 2023)
The fisheries sector is a sector with great potential for the Indonesian economy. East Java has a large fishing business, this is due to the spread of fish landing bases and playing an active role in promoting local fishery production, one of which is the Pondokdadap Coastal Fishing Port (PPP). The purpose of this study was to obtain information about the type and volume of fish caught landed at PPP Pondokdadap in May and June 2022. The method used by the author in conducting this research is through a qualitative descriptive approach. Based on the results of the research, during on May 2022 the production of fish caught landed at PPP Pondokdadap amounted to 1,813.2 tons. Whereas in June the catch amounted to 1,605.9 tons. There were 10 types of fish caught, dominated by tuna. There was a decrease in production volume of 207 tonnes or around 11%.